International Pediatric Otolaryngology Group (IPOG) management recommendations: Pediatric tracheostomy decannulation. (February 2021) - Kennedy, Aimee; Hart, Catherine K.; de Alarcon, Alessandro; Balakrishnan, Karthik; Boudewyns, An; Chun, Robert; Fayoux, Pierre; Goudy, Steven L.; Hartnick, Christopher; Hsu, Wei-Chung; Johnson, Romaine F.; Kuo, Michael; et al.
Abstract: Objectives: To provide recommendations to otolaryngologists, pulmonologists, and allied clinicians for tracheostomy decannulation in pediatric patients. Methods: An iterative questionnaire was used to establish expert recommendations by the members of the International Pediatric Otolaryngology Group. Results: Twenty-six members completed the survey. Recommendations address patient criteria for decannulation readiness, airway evaluation prior to decannulation, decannulation protocol, and follow-up after both successful and failed decannulation. Conclusion: Tracheostomy decannulation recommendations are aimed at improving patient-centered care, quality and safety in children with tracheostomies.